Karakteristik spray diesel dan campuran biodiesel nyamplung pada ruang chamber dengan variasi temperatur ambient - Lukman Hakim; Nasrul Ilminnafik; Gaguk Jatisukamto; Moh. Nurkoyim Kustanto; Andi Sanata (Universitas Muhammadiyah Metro, 2022)
Spray characteristics have an important role in improving the quality of combustion in compression engines. This study analyzes the effect of ambient temperature on spray characteristics including spray tip penetration, spray angle and velocity of spray. The research method uses an experimental method with ambient temperature variations of 60oC, 80oC, 100oC controlled using a thermocouple and an ambient pressure of 0.3 MPa. the composition of the fuel uses diesel (diesel 100%), B30 (30% biodiesel), B100 (100% biodiesel). Image recording using camera speed 480 fms. Based on the experimental results, the ambient temperature increases the spray angle and B100 at all ambient temperatures has a spray tip penetration, velocity of spray is lower.